The implications on challenges faced by rural tourism businesses in Punjab - Kaur, Jasdeep; Chowdhary, Nimit (IJRDO - Journal of Social Science and Humanities Research, 2016)
This research paper seeks to explore the challenges faced by rural tourism businesses and the methods used by the business owners to respond to these within the rural areas of Punjab. There has been little consideration for both of the challenges faced by small scale rural tourism businesses and the methods by which the owners respond to these. Using convenience sampling and case based approach owners of small scale rural tourism businesses in Punjab have been interviewed. The research focuses on the challenges that the owners face and their methods of responses. The common challenges being faced by the rural tourism businesses are in the areas of operations, infrastructure and marketing. The methodology that has been chosen for this research is based in a small geographical location of Punjab that can limit the generalization to other rural locations. These results of this research are of interest to other rural businesses, governments and support organizations. The reason is that these all stakeholders work together to support economical development in rural areas that face industrial restructuring. This research contributes to the discussion of small scale tourism business issues in rural areas and supports efforts to support small scale business creation in relatively disadvantaged rural areas.